Peritoneal Dialysis-related Peritonitis Clinical Outcomes: A systematic review - Kurniawan, Aninditho Dimas; Tjahjodjati, Tjahjodjati (Universitas Aisyah Pringsewu, 2023)
Peritoneal dialysis (PD)-related peritonitis is one of the most common complications and may lead to mechanical failure and death. This may cause by gram-positive, gram-negative, fungal, and sometimes the culture was sterile. This study aims to review the outcomes of PD-related peritonitis. Online searching was performed on PubMed, ScienceDirect, Cochrane, and Google Scholar following PRISMA guidelines. We used the search term peritoneal dialysis, peritonitis, continuous ambulatory peritoneal dialysis, continuous cyclic peritoneal dialysis, and exit-site infection. After a full-text assessment for eligibility, eight articles were included in this review. We found death outcomes were in the range of 1.4 to 9%. Approximately 7.2% to 19.3% were transferred to HD according to four articles. Catheter removal within the range of 5.1% to 25%. Relapse cases varied widely from 1.5% to 12%. Recovery rates were predominant over all of the clinical outcomes from 65% to 82.4%. Although recovery rates of PD-associated peritonitis were high, peritonitis still remained the most common cause of conversion to HD, PD catheter removal, and mortality. Prevention should be the priority to avoid complications and increase mortality rate by daily exit site care and antibiotic prophylactic prior to catheter placement was recommended.